Where has the joy gone? A qualitative exploration of academic university work during crisis and change - Whitsed, Craig; Girardi, Antonia; Williams, John P; Fitzgerald, Scott (Taylor & Francis, 2024)
Universities continue to evolve and adapt to changes brought about by external events such as the COVID-19 pandemic, shifts in government policy, technological advancements, and geopolitics. A significant body of research has focused on negative workplace conditions within universities that contribute to psychosocial hazards. In contrast, this paper reports on the experiences and perceptions of 36 fulltime, continuous, academic staff to explore how they and their colleagues found and/or experienced joy in work set against the backdrop of crisis and change as their universities responded to the impacts of COVID-19. Responses clustered around four key dynamics: joy/student, joy/teaching, joy/research, and joy/colleague. Despite being in work environments characterised largely in negative terms, where agency and voice are constrained, these joys sustained and evoked feelings of purpose, belonging, and connection. This research highlights the need to reconsider how to provide and support healthy work conditions to optimise opportunities for the academic workforce to experience greater joy in their work. The implications for future research are presented.